Atualizações sobre o uso de óleo de peixe no tratamento de cardiopatia canina - Vincenzi, Mariana [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
There are cardiopathies that acometem the dogs, being able this being congenital or acquired and lately have grown the number of cases due to the increase of the life expectancy of these animals becoming each time more necessary prevention methods. In recent years innumerable research is being carried through to understand the influence of the fish oil in the cardiopathies. The fish oil ingestion, Omega 3, has shown beneficial effect in the prevention of cardiovascular illnesses in such a way in the men as in the animals. Such effect this related to the presence of acid greasy polyunsaturateds n-3, mainly acid the eicosapentaenóico (EPA) and acid the docosahexaenóico (DHA). These substances can be found in foods as marine cold water fish (salmon, tuna, sardine and Trout), hemp seeds and soy. The present study, therefore, it has as objective to carry through an update on the use of the fish oil in the treatment of cardiopathies in dogs

São várias as cardiopatias que acometem os cães, podendo estas ser congênitas ou adquiridas. Ultimamente tem crescido o número de casos devido ao aumento da expectativa de vida desses animais tornando-se cada vez mais necessário métodos de prevenção. Nos últimos anos inúmeras pesquisas estão sendo realizadas para compreender a influência do óleo de peixe nas cardiopatias. A ingestão de óleo de peixe, Ômega 3, tem mostrado efeitos benéficos na prevenção de doenças cardiovasculares tanto nos homens como nos animais. Tal efeito esta relacionado à presença de ácidos graxos poliinsaturados n-3, principalmente os ácidos eicosapentaenóico (EPA) e os ácidos docosahexaenóico (DHA). Essas substâncias podem ser encontradas em alimentos como peixes marinhos de águas frias (salmão, atum, sardinha e Truta), sementes de linho e soja. O presente estudo, portanto, tem como objetivo realizar uma atualização sobre a utilização do óleo de peixe no tratamento de cardiopatias em cães
Keywords: Oleo de peixe; Acidos graxos Omega-3; Cão; Cardiopatias - cães; cardiopathies - dogs